High Genetic Diversity and Species Complexity of Diaporthe Associated With Grapevine Dieback in China - Manawasinghe, Ishara S.; Dissanayake, Asha J.; Li, Xinghong; Liu, Mei; Wanasinghe, Dhanushka N.; Xu, Jianping; Zhao, Wensheng; Zhang, Wei; Zhou, Yueyan; Hyde, Kevin D.; Brooks, Siraprapa; Yan, Jiye (Frontiers in Microbiology, 2019)
Grapevine trunk diseases have become one of the main threats to grape production worldwide, with Diaporthe species as an emerging group of pathogens in China. At present, relatively little is known about the taxonomy and genetic diversity of Chinese Diaporthe populations, including their relationships to other populations worldwide. Here, we conducted an extensive field survey in six provinces in China to identify and characterize Diaporthe species in grape vineyards. Ninety-four isolates were identified and analyzed using multi-locus phylogeny. The isolates belonged to eight species, including three novel taxa, D. guangxiensis, D. hubeiensis, D. viniferae, and three new host records, D. gulyae D. pescicola and D. unshiuensis. The most commonly isolated species was D. eres. In addition, high genetic diversity was observed for D. eres in Chinese vineyards. Haplotype network analysis of D. eres isolates from China and Europe showed a close relationship between samples from the two geographical locations and evidence for recombination. In comparative pathogenicity testing, D. gulyae was the most aggressive taxon, whereas D. hubeiensis was the least aggressive. This study provides new insights into the Diaporthe species associated with grapevines in China, and our results can be used to develop effective disease management strategies.